Cognitive symptoms of Alzheimer's disease: clinical management and prevention. (6th December 2019) - Joe, Elizabeth; Ringman, John M
ABSTRACT: Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the accumulation of amyloid β in the form of extracellular plaques and by intracellular neurofibrillary tangles, with eventual neurodegeneration and dementia. There is currently no disease-modifying treatment though several symptomatic medications exist with modest benefit on cognition. Acetylcholinesterase inhibitors have a consistent benefit across all stages of dementia; their benefit in mild cognitive impairment and prodromal AD is unproven. Memantine has a smaller benefit on cognition overall which is limited to the moderate to severe stages, and the combination of a cholinesterase inhibitor and memantine may have additional efficacy. Evidence for the efficacy of vitamin E supplementation and medical foods is weak but might be considered in the context of cost, availability, and safety in individual patients. Apparently promising disease-modifying interventions, mostly addressing the amyloid cascade hypothesis of AD, have recently failed to demonstrate efficacy so novel approaches must be considered.